Material sensoriomotriz para fortalecer el desarrollo de las capacidades cognitivas de los niños y niñas con síndrome de down de la Unidad Educativa Especializada de Cotopaxi, en la provincia de Cotopaxi, cantón Latacunga, parroquia Ignacio Flores en el periodo 2014-2015 - Almache Tigse, Emilia Maribel (2015)
This research is based on the importance of sensorimotor material in the process of teaching and learning and cognitive development of children with Down syndrome. Various research indicates that teaching material takes on a crucial role when working with childrens with special needs, because the sensory development is the starting point in the acquisition of knowledge and skills, because if the child maintains contact directly with objects in their environment through their senses, you will have optimal development not only in the cognitive area, but also in the areas of language, motor and socio-emotional. The present work is a non-experimental study, framed in feasible project methodology, because of a problem is identified and a didactic proposal is designed to solve it. To do the interviewing techniques, survey and observation was applied and as instruments questionnaire and checklist was used. Regarding the results of the investigation, the guide was obtained for the development of sensorimotor material for the development of each of the senses, which included fifteen different workshops teaching resources, to strengthen the cognitive area of children with Syndrome Down.